The Aerodynamics of High Speed Aerial Weapons - Prince, Simon A. (Cranfield University, 1999)
The focus of this work is the investigation of the complex compressible flow phenomena associated with high speed aerial weapons. A three dimen- sional multiblock finite volume flow solver was developed with the aim of studying the aerodynamics of missile configurations and their component structures. The first component of the study involved the aerodynamic investigation of the isolated components used in the design of conventional missile config- urations. The computational study of nine ogive-cylinder body experimental test cases is presented together with a new interpretation of the complex vortical flow including the windward appearance of a "vortex shock wave". In addition, a simple modification to improve the accuracy of the Baldwin- Lomax/Degani-Schi fl`' turbulence model is put forward, and the phenomenon of "phantom vorticity" in Euler solutions and its alleviation are described. Inclined Delta Wings in supersonic flow were computed in order to study the aerodynamics of wings alone, and in particular the vortex-shock interactions which occur on their leeward surfaces. The second component of the study was the computational and experimen- tal investigation of a generic cruciform missile configuration. The compli- cated interactions between shock waves and boundary/shear layers that are seen to occur around and in the wake of the cruciform wing arrangement were studied and described. The third component of the research involved an assessment of the pre- diction technologies used in the design of modern weapons. In particular the role of Computational Fluid Dynamics in the process of design.